EFFECT SELF EFFICACY, ENTREPRENEURSHIP EDUCATION AND SUBJECTIVE NORMS ON STUDENT ENTREPRENEURSHIP BEHAVIOR FKIP JAMBI UNIVERSITY - Nopriadi, Syahrul; Khairinal, Khairinal; Rosmiati, Rosmiati (Universitas Bunda Mulia, 2022)
High student interest in entrepreneurship is not accompanied by a decision or behavior for entrepreneurship. The purpose of this study was to test and analyze self-efficacy, entrepreneurship education, and subjective norms on the entrepreneurial behavior of FKIP Jambi University students. The approach used in this research is a quantitative approach. The sample in this study was 296 FKIP Jambi University students who were selected based on probability sampling technique. Analysis and processing of data using path analysis. Based on the data analysis of variables 1) there is a direct influence of self-efficacy on the subjective norm of 0.368; 2) there is a direct influence of entrepreneurship education on the subjective norm of 0.585; 3) there is a direct influence of self-efficacy on entrepreneurial behavior 0.419; 4) there is a direct influence of entrepreneurship education on entrepreneurial behavior of 0.190; 5) there is a direct influence of subjective norms on entrepreneurial behavior 0.306; 6) the effect of total self-efficacy on entrepreneurial behavior through the subjective norm intervening variable 0.532; 7) the total influence of entrepreneurship education on the entrepreneurial behavior variable through the subjective norm intervening variable with a total influence value of 0.369.